Measuring Marketing : The 100+ Essential Metrics Every Marketer Needs 3rd Edition - Davis, John A. (Boston ; Berlin : De|G Press, 2017)
Marketing has long been considered more art than science, but the demands of a more dynamic, globalized business world has led to the development of sophisticated methods for quantifying marketing success. Organized into eleven focused sections, this reliable resource offers an effective approach to making a complex topic understandable. Written for both marketing managers accountable for growth-driven activities that must yield measurable results as well as senior executives who need a firm understanding of marketing's impact on a business or product line, this informative guide puts more than 110 key metrics in perspective. Along the way, you'll be introduced to a variety of important analytical tools, from brand, customer, and sales metrics to advertising, price, and distributions metrics. And with the addition of new examples and metrics-including significant updates to the online/digital/social area- Measuring Marketing, Third Edition will put you in a better position to excel at this difficult endeavor.
Frontmatter -- Praise For Measuring Marketing, Third Edition / Bodell, Lisa / Farrell, Mark / Nair, Hari / McCabe, Thomas / Leonard, Steve / Vallisuta, Pakpoom -- About The Author -- Contents -- Introduction -- Part 1: Corporate Financial Metrics -- Part 2: Marketing Planning Measures -- Part 3: Brand Metrics -- Part 4: Customers Metrics -- Part 5: Product/Offering Metrics -- Part 6: Price Metrics -- Part 7: Advertising/Promotion Metrics -- Part 8: Direct Marketing Metrics -- Part 9: Digital/Social Metrics -- Part 10: Place/Distribution Metrics -- Part 11: Sales Metrics
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jan 2018)
Keywords: Metrics, Data-driven, Analytics, Marketing performance, Quant